Pemetrexed versus erlotinib in pretreated patients with advanced non–small cell lung cancer: A Hellenic Oncology Research Group (HORG) randomized phase 3 study. Issue 15 (9th May 2013) - Karampeazis, Athanasios; Voutsina, Alexandra; Souglakos, John; Kentepozidis, Nikos; Giassas, Stelios; Christofillakis, Charalambos; Kotsakis, Athanasios; Papakotoulas, Pavlos; Rapti, Ageliki; Agelidou, Maria; Agelaki, Sofia; Vamvakas, Lambros; et al.
Abstract : BACKGROUND: In this superiority study, pemetrexed was compared with erlotinib in pre‐treated patients with metastatic non–small cell lung cancer (NSCLC). METHODS: Patients with stage IIIB/IV NSCLC who progressed after first‐line or second‐line treatment were randomized to receive either pemetrexed or erlotinib. In total, 21.7% of patients in the pemetrexed arm and 23.5% of patients in the erlotinib arm had squamous cell histology, and treatment was third line in 39.2% and 46.4% of patients, respectively. The primary study endpoint was time to tumor progression (TTP). Epidermal growth factor receptor/v‐Ki‐ ras 2 Kirsten rat sarcoma viral oncogene homolog ( EGFR / KRAS ) mutation status also was investigated. RESULTS: There was no difference in terms of the TTP ( P  = .195), the objective response rate ( P  = .469), or overall survival ( P  = .986) between the 2 treatment arms. In patients who had squamous cell histology, erlotinib resulted in a superior TTP compared with pemetrexed (4.1 months vs 2.5 months, respectively; P  = .006). The incidence of grade 3 and 4 neutropenia, thrombocytopenia, and asthenia was significantly higher in the pemetrexed arm, whereas the incidence of grade 3 and 4 skin rash was higher in the erlotinib arm. CONCLUSIONS: Both pemetrexed and erlotinib had comparable efficacy in pre‐treated patients with metastatic NSCLC, and the current results indicated that genotyping of tumor cells may have an important effect on treatment efficacy. Cancer 2013 ;119:2754–2764. © 2013 American Cancer Society . Abstract : Both pemetrexed and erlotinib are active in patients with pretreated non–small cell lung cancer (NSCLC). In this randomized controlled phase 3 trial, the 2 drugs are compared, and the results indicate that both agents are equally effective in unselected patients with previously treated NSCLC, although they have different toxicity profiles. Exploratory biomarker analyses indicate no difference in efficacy irrespective of EGFR status, whereas the presence of KRAS mutations is correlated with treatment efficacy.